Conditions of hazardous waste management in Poland in the context of circular economy - Pyssa Justyna (EDP Sciences, 2021)
Along with the increase of disproportions between the rapidly growing demand for raw and essential materials and limited possibilities of obtaining them, the economy of raw and essential materials becomes the main problem of contemporary and future social and economic politics. One of the important areas of reducing this disproportion is the limitation of intensity of waste generation during production and more consistent management of accumulated waste and waste generated on a daily basis. At the same time it is a major problem of obtaining secondary raw materials and the environment protection. The selection of technology of hazardous waste disposal should take place according to the principle of circular economy. It means that the rational waste management, taking into account both ecological and economic factors, enforces the demand for maximizing the utilization of waste in all possible applications while limiting its negative impact on the environment at the same time. In the article legal acts regulating the management of hazardous waste have been analyzed. Economic and ecological criteria of the selection of technology of disposal of hazardous waste have been analyzed.